Assessment of obstetric and gynaecological problems in females with bleeding disorders - Panchbudhe, Shruti Ashok; Desai, Ashwini Sudhir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Inherited bleeding disorders are not common but they are lifelong. Their effects on women are far greater than previously realised. Many clinicians are not familiar with these disorders but may encounter such women under acute conditions. Objectives were to study various obstetric and gynaecological problems in females with bleeding disorders and to assess the type of management given for these disorders. Methods: This was a prospective observational study carried out at Department of Obstetrics and Gynaecology at a tertiary care hospital in which 30 women of known bleeding disorder were studied and various obstetric and gynaecological problems including menorrhagia, metrorrhagia, dysmenorrhoea, mid-cycle pain, conception, haemorrhagic ovarian cyst, etc. were identified and studied in them. Results: 30 patients of known bleeding disorder who were found to have obstetric and gynaecological problem were studied. Idiopathic thrombocytopenic purpura constituted the major bleeding disorder (23%), followed by von Willebrand’s disease (17%) in our study. 21 patients had gynaecological problem and the most common gynaecological problem was menorrhagia (62%), followed by hemoperitoneum (10%), mid cycle pain (10%), persistent haemorrhagic cyst (7%), dysmenorrhea (7%) and endometriosis (4%). 20 patients had obstetric problems of which postpartum haemorrhage (59%) was a major problem followed by recurrent pregnancy loss (33%) and infertility (8%). The study concluded that both obstetric and gynaecological problems are common in patients of bleeding disorders and occur in distribution 66.66% and 70% respectively. Conclusions: The study conducted shows that obstetric and gynaecological problems are very common in patients of bleeding disorders and thus optimal management of these problems requires a multidisciplinary team of approach.